2016
DOI: 10.1111/aphw.12064
|View full text |Cite
|
Sign up to set email alerts
|

Oops I Did it Again: Examining Self‐Licensing Effects in a Subsequent Self‐Regulation Dilemma

Abstract: The results obtained suggest that self-licensing negatively affects goal re-engagement in the same situation, but not in a new situation. Whether self-licensing maintains or increases feelings of self-efficacy needs to be validated in future studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 66 publications
(88 reference statements)
0
20
1
Order By: Relevance
“…Indeed, as a recent randomized controlled trial of a different alcohol reduction app suggests [13], care needs to be taken that content is used as intended, and not as a means to accurately quantify reductions in drinking at one point in time in order to give license to engage in different, yet equally damaging, drinking patterns at a later date [27]. …”
Section: Discussionmentioning
confidence: 99%
“…Indeed, as a recent randomized controlled trial of a different alcohol reduction app suggests [13], care needs to be taken that content is used as intended, and not as a means to accurately quantify reductions in drinking at one point in time in order to give license to engage in different, yet equally damaging, drinking patterns at a later date [27]. …”
Section: Discussionmentioning
confidence: 99%
“…For example, recent reviews showed that stress impairs efforts to be physically active, and stress and negative emotions unfavorably in uences dietary behavior (26)(27)(28)(29); however, evidence for an association between negative emotions and physical activity remains inconclusive (30,31). Furthermore, indulgence has been associated with unhealthy eating behavior by multiple studies, especially when the indulgence is justi ed ("I worked so hard today, I deserve it") (32,33). Despite the indicated association between lifestyle imbalance and relapse according to the RPM, studies assessing this potential association are, to our knowledge, currently lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, this secondary effect pertaining to how goal violations are incorporated into one’s self-perceptions, may point to a positive side of self-licensing. Indeed, a recent vignette study showed that when participants imagined themselves in a situation where they violated their diet with a license, they subsequently reported higher feelings of self-efficacy than participants who did not have a license for this transgression ( Prinsen et al., 2016 ). This finding supports our proposition that self-licensing helps maintain or may even increase perceived self-regulatory ability because it determines how self-regulation “failure” is interpreted.…”
Section: Self-licensing and Perceived Self-regulatory Abilitymentioning
confidence: 99%
“…Specifically, the observation that self-licensing leads to resolution of self-regulatory conflict, albeit to the advantage of the temptation, may imply that self-perceptions of being an effective self-regulator are protected. That is, through self-licensing, a goal violation is perceived as more justified ( Prinsen, Evers, & de Ridder, 2016 ), and presumably experienced less as failure. Importantly, this may in turn influence how subsequent temptations are handled.…”
mentioning
confidence: 99%